Characterization of Metal Dispersion of Some Naphtha Reforming Catalysts by Methylcyclohexane Dehydrogenation Reaction - Ali, Ahmed J.; Rahman, Ameel Mohammed (Al-Khwarizmi Engineering Journal, 2009)
The dispersion of supported Pt and Pt–Ir reforming catalysts have been studied, after treatment with oxidative and reducing atmosphere. Methylcyclohexane dehydrogenation reaction in the absence of hydrogen was used as a test reaction. An attempt was made to relate the behavior of the catalysts upon subject to reaction, to the dispersion of the same type of catalysts upon treatment with similar atmosphere and temperatures which appeared in literature. The total conversion of reaction can be explained by a change in metal dispersion. Thus, methylcyclohexane dehydrogenation reaction appears to be a really “structure sensitive” reaction.      The toluene yield increases as the oxidation temperature increases over the studied catalyst RG-402, RG-412, RG-422 and RG-432 respectively and reached a maximum value at 550°C. Above 550 the conversion decreases due to the effect of catalyst sintering.      No significant change were observed for reduction temperature range 400-600°C for the above studied catalysts.      The selectivity order for the studied catalysts and for reduction treatment experiments arranged asfollows:RG-422> RG-432> RG-412> RG-402